2013
DOI: 10.1159/000355108
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Optical Coherence Tomography Findings in Acute Zonal Occult Outer Retinopathy

Abstract: Purpose: To report a case of acute zonal occult outer retinopathy (AZOOR) in a 39-year-old woman. Methods: Images were obtained with fundus photography and optical coherence tomography (OCT). A multifocal electroretinogram (mfERG) was also obtained to evaluate retinal function. Results: The patient's right visual acuity was 0.8. Fundus photographs showed no specific abnormal findings. OCT showed attenuation of the photoreceptor inner segment/outer segment (IS/OS) line and the cone outer segment tip (COST) line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…12 Abnormalities of the cone outer segment tip (COST) line have been reported in AZOOR. 13 COST line has been recognised in SD-OCT images as a thin, highly reflective line between the IS/OS junction and the RPE. 14 The characteristic features described in the recent original investigation by Mrejen et al included a demarcating line of the progression at the level of the outer retina and a trizonal pattern of sequential involvement of the outer retina, RPE and choroid, as well as frequent zonal progression.…”
Section: Discussionmentioning
confidence: 99%
“…12 Abnormalities of the cone outer segment tip (COST) line have been reported in AZOOR. 13 COST line has been recognised in SD-OCT images as a thin, highly reflective line between the IS/OS junction and the RPE. 14 The characteristic features described in the recent original investigation by Mrejen et al included a demarcating line of the progression at the level of the outer retina and a trizonal pattern of sequential involvement of the outer retina, RPE and choroid, as well as frequent zonal progression.…”
Section: Discussionmentioning
confidence: 99%
“…A discrepancy between microstructural findings and retinal function recovery has been reported but in that case, there was a partial restoration of the EZ but no improvement of the visual function. 11 It has been also reported that damaged human photoreceptor outer segments are capable, under certain circumstances, of spontaneous regeneration. 17 The cellular events underlying this gradual regeneration are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic SD-OCT findings in AZOOR include disruption or loss of the EZ, attenuation or loss of the outer nuclear layer (ONL) and/or the external limiting membrane, irregularity of the RPE such as the abnormalities or absence of the interdigitation zone (IDZ) or the cone outer segment tip (COST) line, and decreased retinal thickness. 911 All these abnormalities are probably due to the impairment of photoreceptors, although the mechanism of vision loss in AZOOR patients remain unclear. Mrejen et al proposed a classification of AZOOR complex disease based on clinical fundus and modern multimodal imaging, including SD-OCT, FAF, FA and ICG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large blind spot syndromes include the Acute Zonal Occult Outer Retinopathy (AZOOR) (39). The OCT features in AZOOR are well-recognized and consist of disruption of the inner outer segment and changes on autofluorescence (40,41). For OCT research, AZOOR provides a model for the study of acquired anterior axonal degeneration in the retina that starts distal to the INL.…”
Section: Acute Zonal Occult Outer Retinopathy Spectrummentioning
confidence: 99%